Implementasi Ekstrakurikuler Pendalaman Agama Terhadap Penanaman Nilai Religius Siswa - Nisak, Zuhrotun; ., syamsul; ., istiqomah; Hasan, Nur; Rohmatul Fauziyah, Nina (Jurnal Murid, 2024)
Education is very important for the development of life, improving the quality of life, both in terms of science, behavior and its benefits in society. Therefore, education must always be developed in accordance with the developments and demands of the times, including religious education. This is contrary to the reality that exists in social life as a result of social changes, religious values are not given enough attention. This study aims to find out how the implementation of the Religious Deepening extracurricular towards instilling students' religious values, what are the supporting and inhibiting factors in its implementation. The inculcation of religious values in students is a reference for the formation of a personality with good morals who believes and fears Allah SWT. The method used in this research is a qualitative approach. The results showed that the Religious Deepening extracurricular activities at MA Al- Munawwaroh Kembangbahu were activities carried out to explore religious material and student personality. The implementation of this Religious Deepening extracurricular activity includes materials that will be delivered by the mentor. The method used is the lecture or story method, discussion and demonstration. Each mentor uses this method and adjusts the conditions of the students participating in the activity. Supporting factors in the implementation of the Religious Deepening extracurricular include: creative and innovative educators, the interests and talents of students, the desire and support from parents, adequate facilities, which are the difference between madrasas and public schools. While the inhibiting factors in this implementation are the lack of response from students, limited time for activities, lack of communication between parents, students, and educators, and playing gadgets.